Estudios taxonómicos, ontogenéticos, ecológicos y etológicos sobre los ostrácodos de agua dulce en colombia v. - estudio taxonómico del género chlamydotheca saussure 1858, (ostrácoda, podocopida, cyprididae) parte i. aspectos morfológicos de una nueva esp (1985)
The present study works out generic characteristics of the external morfology of the carapax, the chitinous skeleton and of some morfological aspects concerning the articulation of the extremities in the case of a new species of the genus Chlamydotheca Saussure, 1858 (loc, typ.: Colombia, valle del rio Cauca, ciudad de Cali).